Professional stress of special school teachers in Palakkad District - K.V., Radha; Mohana, D. (Gyan Management Journal, 2022)
The present study is aimed to find out the professional stress of special  school teachers in Palakkad district, Kerala State. Data were collected from  50 special school teachers dealing students with LD,HI,VI,MR and Autism  by administering professional stress scale developed by the researcher  and her supervising teacher. Teachers with average stress are 76%where  as teachers with severe stress and low stress are 16% and 8% respectively.  There is no significant difference in professional stress based on gender, type  of management and teaching experience. Among the various components  contributing to professional stress, students’ behaviour and parental  involvement are more influential than rest of them. The least influential  components are working environment and administrative norms. The  findings indicate the need to empower special school teachers in the district  to deal students and their parents in a most pleasing and diplomatic way. .
Keywords: Professional stress; Special school teachers